The River of Ambrosia: An Alternative Commentarial Tradition of the Bhāgavata Purāṇa. (23rd June 2018) - Venkatkrishnan, Anand
Abstract: Although the Bhāgavata Purāṇa, one of the most famous Hindu scriptures, found its final form around the tenth century CE, the first extant commentaries on the text date from a full three to four centuries later. This essay analyses for the first time an unpublished commentary on the Bhāgavata called the Amṛtataraṅgiṇī, or the River of Ambrosia, written around the same time as its more famous counterpart, the Bhāvārthadīpikā by Śrīdhara. I argue that the River of Ambrosia is one member of an entirely alternative commentarial tradition, one that circumvented the geographical routes and religious affinities that scholars have associated with the reception history of the Bhāgavata . My essay focuses on two features of the River of Ambrosia : philosophy and aesthetics. Finally, I make a case for the alternativeness of this tradition qua tradition, in light of its later appropriation in sixteenth-century Kerala.